Comparative Analysis of Spatial-Time Harmonics of Radial Forces in the Multi-Phase Synchronous Reluctance Machines of Three- Six- and Nine- Phase Winding - Jędryczka, Cezary; Mysiński, Michał; Macyszyn, Łukasz (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
The paper deals with analysis of radial forces in the multi-phase synchronous reluctance machines (SynRM). SynRM of three-, six- and nine-phase windings were studied. The field models were developed to determine normal and tangential components of magnetic flux density vector in the air-gap of the studied machines. The selected research results have been presented and discussed.